2005
DOI: 10.1074/jbc.m506569200
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational Regulation of Adipose Differentiation-related Protein by the Ubiquitin/Proteasome Pathway

Abstract: Adipose differentiation-related protein (ADRP) is localized to lipid droplets in most mammalian cells. ADRP, proposed to regulate fatty acid mobilization and lipid droplet formation, is linked to lipid accumulation in foam cells of human atherosclerotic lesions. In this report, we show that ADRP protein accumulates in Chinese hamster ovary fibroblastic cells cultured in the presence of oleic acid but is destabilized when fatty acid sources are removed from culture serum. The latter effect was blocked by the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
244
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 239 publications
(265 citation statements)
references
References 53 publications
18
244
2
1
Order By: Relevance
“…It has been noted that lipid loading by supplementing fatty acids in the culture medium could enhance the accumulation of other LD-associated proteins, including ADRP, perilipin, and caveolin-1 (25,26,28,29). Here, a gradual increase in Fsp27 accumulation in the presence of exogenous fatty acids was also observed in 3T3-L1 adipocytes.…”
Section: Fsp27 Is Stabilized By ␤-Agonistsupporting
confidence: 50%
See 1 more Smart Citation
“…It has been noted that lipid loading by supplementing fatty acids in the culture medium could enhance the accumulation of other LD-associated proteins, including ADRP, perilipin, and caveolin-1 (25,26,28,29). Here, a gradual increase in Fsp27 accumulation in the presence of exogenous fatty acids was also observed in 3T3-L1 adipocytes.…”
Section: Fsp27 Is Stabilized By ␤-Agonistsupporting
confidence: 50%
“…Substitution of these lysine residues with alanines led to significantly reduced Fsp27 ubiquitination and increased stability. It has been shown that several other LD-associated proteins, such as ADRP, perilipin, and Cidea, have varying halflives and are all subjected to the ubiquitin-dependent degradation pathway (13,(25)(26)(27). Thus, our current work suggests a general role for ubiquitination-mediated protein degradation in the regulation of LDassociated proteins.…”
Section: Fsp27 Is Stabilized By ␤-Agonistmentioning
confidence: 68%
“…3). CHO-K1 cells expressing mATGL(S47A)-CFP alone or co-expressing mATGL(S47A)-CFP and CGI-58-YFP were incubated overnight with 400 M oleic acid to increase LD formation and levels of endogenous perilipin 2 on LDs (35). Co-expression of CGI-58-YFP with mATGL(S47A)-CFP increased recruitment of mATGL to LDs, when compared with results obtained in cells expressing only mATGL(S47A)-CFP (Fig.…”
Section: Localization Of Cgi-58 In Cells Expressing Perilipins 1 2 mentioning
confidence: 99%
“…ADFP mainly targets the lipid droplet surface, and unbound ADFP protein is rapidly degraded (20). These differences in lipid droplet binding characteristics and/or stability in aqueous environment may be responsible for the lack of Tip47 overexpression observed in the ADFP null mouse tissues studied (26).…”
Section: Discussionmentioning
confidence: 99%
“…4 On the other hand, we have reported that protection of ADFP from proteosomal degradation with the inhibitor, MG-132, is accompanied by a substantial increase (170%) in lipid content compared with control cells untreated with MG-132, suggesting that ADFP, like perilipin, protects neutral lipids from degradation by lipases (20,21).…”
mentioning
confidence: 99%